Biosorption 2018
DOI: 10.5772/intechopen.77315
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biosorption for Removal of Heavy Metals from Wastewater

Abstract: Fresh water accounts for 3% of water resources on the Earth. Human and industrial activities produce and discharge wastes containing heavy metals into the water resources making them unavailable and threatening human health and the ecosystem. Conventional methods for the removal of metal ions such as chemical precipitation and membrane filtration are extremely expensive when treating large amounts of water, inefficient at low concentrations of metal (incomplete metal removal) and generate large quantities of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
129
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(134 citation statements)
references
References 182 publications
(124 reference statements)
0
129
0
5
Order By: Relevance
“…In the metabolism dependent biosorption, precipitation occurs as a response by the microorganisms' active defence system in the presence in an environment containing toxic metal ions (Perpetuo et al, 2011). In the metabolism independent biosorption, precipitation occurs due to chemical reactions between the functional groups of the cell wall of the biosorbent and the metal ion, the reactions may involve oxidation-reduction reactions (Kanamarlapudi et al, 2018). A study confirmed the…”
Section: Precipitationmentioning
confidence: 79%
See 4 more Smart Citations
“…In the metabolism dependent biosorption, precipitation occurs as a response by the microorganisms' active defence system in the presence in an environment containing toxic metal ions (Perpetuo et al, 2011). In the metabolism independent biosorption, precipitation occurs due to chemical reactions between the functional groups of the cell wall of the biosorbent and the metal ion, the reactions may involve oxidation-reduction reactions (Kanamarlapudi et al, 2018). A study confirmed the…”
Section: Precipitationmentioning
confidence: 79%
“…Simple diffusion is also a basic mechanism observed in most types of biosorption (Sao, 2014). Several factors can contribute in controlling the mechanisms, those include the chemical, stereochemical and coordination characteristics of the metal of interest which involves the ion mass, ionic radius and the oxidation state of the metal ion (Kanamarlapudi, Chintalpudi, & Muddada, 2018). The properties of the biosorbent of choice also affect the mechanism of biosorption, properties such as the number of reactive binding sites, accessibility and availability of binding sites, type of binding site and the affinity between the binding site of the biosorbent and metal ion of interest (Abdi & Kazemi, 2015).…”
Section: Mechanisms Of Biosorptionmentioning
confidence: 99%
See 3 more Smart Citations